Examining widely held propositions on human dietary protein needs and benefits: a critical review of the science that shapes both the data and our understanding of an essential macronutrient - Mitchell M. Kanter; Sally Aaron; Steven N. Austad; Andrew W. Brown; Nicholas A. Burd; Wayne W. Campbell; Mark Cope; Teresa A. Davis; John W. Erdman; Miguel Freitas; Kristen Hicks-Roof; Samuel Klein; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Differences in Siderophore Production During the Growth of Phytoplankton in Southern Ocean Incubation Experiments Under High‐ and Low‐Iron Conditions - Randelle M. Bundy; Kristen N. Buck; Bethany D. Jenkins; P. Dreux Chappell; Daniel J. Repeta; Alexa Sterling; Shannon M. Yang; Laura Holland; Léo Mahieu; Laura E. Moore (Environmental Microbiology, 2026)
Iron is an important micronutrient required by marine microorganisms. The Southern Ocean is an ecosystem where primary production is limited by the availability of iron, but how microorganisms in this region adapt to low‐iron conditions or respond to episodic iron inputs is understudied. We tested how external iron additions would impact bacterial production of siderophores during phytoplankton growth using shipboard incubation experiments under a range of iron conditions. Similar heterotrophic bacteria communities and phytoplankton biomass were observed whether iron was added from the continental margin or as inorganic iron. Under both high‐ and low‐iron conditions, the heterotrophic bacteria community remained the same but produced distinct iron‐binding siderophores. Siderophores were detected in the highest concentrations when phytoplankton and heterotrophic bacteria were iron‐limited, and unique compounds were produced in low‐iron conditions compared to when iron was added. Hydrophobic siderophores dominated when iron concentrations were low, and hydrophilic compounds when iron concentrations were higher, and this was likely due to environmental factors rather than changes in the microbial siderophore producers. Our results also highlight that phytoplankton growth likely played an important role in stimulating siderophore production across both low‐ and high‐iron conditions, with important implications for phytoplankton and bacteria interactions.

Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

Tooth morphology of deep‐water catsharks of the genus Apristurus (Chondrichthyes: Pentanchidae) in the North Atlantic Ocean - Jesco Seifert; Daniel M. Moore (Journal of Fish Biology, 2026)
The deep‐water catshark family (Pentanchidae) is the most species‐rich family among extant shark lineages. Within this family, the genus Apristurus is the largest, comprising small, deep‐sea species characterised by elongated bodies and dorso‐ventrally compressed snouts. Five Apristurus species are currently recognised from the North Atlantic, including waters surrounding Ireland and the United Kingdom ( A. aphyodes , A. laurussonii , A. manis , A. melanoasper and A. microps ). However, their biology remains poorly understood owing to their occurrence at considerable depths and their close morphological similarity. This study presents the first comprehensive comparative analysis of tooth morphology for Apristurus species recorded in the region. The results reveal pronounced sexual dimorphism in A. aphyodes and provide evidence supporting ontogenetic changes in tooth morphology in A. melanoasper and A. microps . Furthermore, distinctive morphological characteristics are identified and described for each species using scanning electron microscopy of the dentition. These findings establish novel diagnostic criteria that enhance the reliability of species identification and provide a robust framework for future taxonomic and ecological research.

Longitudinal associations of cardiorespiratory fitness and physical activity with changes in cognitive function in breast cancer patients undergoing chemotherapy: a prospective matched-control study - Hui Xiao; Ellen Warner; Jennifer Ryan; Catherine Sabiston; Golnaz Ghazinour; Sarah O’Rourke; Daniel Moore; Timothy Welsh; Linda Trinh (Cancer Causes & Control, 2026)

EQual Rubric Evaluation of the Radiation Oncology Education Collaborative Study Group Entrustable Professional Activities - Brett Wagner; Steve Braunstein; Ryan Brisson; Alexandra De Leo; Allison Garda; Jillian Gunther; Christina Henson; Ariel E Hirsch; Jordan Holmes; Leah Katz; Malcolm Mattes; Jessica Moore Schuster; et al. (Journal of Cancer Education, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Charge measurements for optimised NOM characterisation and removal by coagulation - Daniel Ruth; Bruce Jefferson; Ryan Pereira; Graeme Moore; Peter Jarvis (Journal of Water Process Engineering, 2026)

The indicator amino acid oxidation (IAAO) technique: a novel approach to assess protein intakes that maximize whole-body protein anabolism - Julia M. Malowany; Glenn A. A. van Lieshout; Lex B. Verdijk; Daniel R. Moore; Luc J. C. van Loon; Jorn Trommelen (Critical Reviews in Food Science and Nutrition, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

PoreViT: Automated pore typing in carbonate rocks using vision transformers and neighborhood features - Yemna Qaiser; Mohammed Ishaq; Mohammed Yaqoob; Mohammed Yusuf Ansari; Isaac Sujay; Talha Khan; Harris Rabbani; Juan Carlos Laya; P.J. Moore; Thomas Daniel Seers (Computers & Geosciences, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Evaluation of proinsulin(F25D) as a targeting ligand for insulin-binding B cells in autoimmune diabetes - Kyle D. Apley; Lindsay E. Bass; Jaylyn King; Grant Downes; Kristen Wang; Mason V. Forchetti; Daniel J. Moore; Peggy Kendall; Rachel H. Bonami; Cory J. Berkland (Drug Delivery and Translational Research, 2026)

Divergent responses of seed banks and aboveground vegetation to drought and deluge in grasslands across an elevational gradient - Jennifer R. Gremer; Margaret M. Moore; Daniel C. Laughlin; Seth M. Munson (Oecologia, 2025)

Increasing Prostate Cancer Education and Screening for Black Men in Southeastern Michigan: Your Prostate, Your Health - Shane A. Tinsley; Doreen Dankerlui; Camille Romain; Wilma Ruffin; Eric Brown; Clarence Burnett; Donna Long; Karen Yacobucci; Jaye Clement; Abisola Fasakin; Biola Makinde-Odusola; Eric Williams; et al. (Journal of Cancer Education, 2025)

Population Genomics and the Environmental Drivers of Population Structure in a Cosmopolitan Marine Predator, Tursiops truncatus - Daniel M. Moore; Andre E. Moura; Ada Natoli; Elena Papale; Emily G. Cunningham; Mónica A. Silva; Tilen Genov; Stefania Gaspari; Giuseppa Buscaino; Per Berggren; Darren R. Gröcke; A. Rus Hoelzel (Molecular Ecology, 2025)
The marine environment comprises vast regions without physical barriers to movement, making the understanding of population isolation and the evolution of diversity challenging. This is especially the case for highly mobile marine species. Here we investigate populations of the common bottlenose dolphin ( Tursiops truncatus ) across the Mediterranean Sea and adjacent North Atlantic using high‐resolution genomic markers (RADseq) and stable isotope analyses to better understand the evolution of population structure in this system. High‐resolution genomic data and broad geographic sampling revealed patterns of structure not previously identified, and integration with stable isotope data suggests that prey choice varies across this region. Unexpected patterns included genetic and isotopic similarity between the North Atlantic and the region around Sicily (but not including the medially located Gulf of Cádiz and surrounding regions). The regional habitat within and beyond the Mediterranean Sea is structured with ocean frontal systems including thermal and halocline transitions, several of which show alignment with genetic transitions within our data. Our data help to distinguish among possible drivers of population differentiation for a marine predator that has the potential for long‐distance dispersion.

The Evolution of Southern Ocean Net Primary Production in a Changing Climate: Challenges and Opportunities - Alessandro Tagliabue; Thomas Ryan‐Keogh; Alex Baker; Thomas S. Bibby; Chris Follett; Maeve C. Lohan; Alberto Naveira‐Garabato; Daniel J. Mayor; Angela Milne; C. Mark Moore; Simon Ussher (Global Change Biology, 2025)
Net primary production in the Southern Ocean plays a critical role in governing ecosystem production, the biological carbon pump, and global biogeochemical cycles. Recent work has advanced our understanding of novel factors regulating Southern Ocean net primary production and the regional physiological adaptations employed by Southern Ocean phytoplankton in terms of their photosynthetic strategies and resource acquisition. Here we assess trends in Southern Ocean net primary production from different remote sensing algorithms and bgc‐Argo floats to compare them to the latest Earth System Models used to forecast future changes under three different future climate scenarios. Overall, remote sensing and bgc‐Argo floats indicate net primary productivity in the Southern Ocean is declining at basin scale. This contrasts with the Earth System Models that display muted contemporary trends and consistent increases in net primary production that are relatively robust across SSP2‐45, SSP3‐70, and SS5‐85. This mismatch in trends suggests low confidence in these projected net primary production changes, with implications for assessments of changes in ecosystem services. Despite their coherence in terms of net primary production trends, Earth System Models show large disagreement in the relative role of different drivers, suggesting we lack sufficient mechanistic understanding. Improved knowledge of the role of manganese alongside iron and the coupled responses of phytoplankton and zooplankton through the integration of observations and experiments into a new generation of models is necessary to deliver confident forecasts of Southern Ocean ecosystem change. Advancing knowledge in these areas is an important priority for future research in the region and provides context for policy discussions around the marine protection of Antarctic ecosystems that depend on sufficiently confident projections of climate change impacts.

Development and testing of a continuous maritime monitor for radionuclide aerosols - Michael E. Moore; Martin E. Keillor; Daniel Cain; Thomas W. Hallen; Jared C. Johnson; Dustin M. Kasparek; Sarah A. Mendoza; Cory T. Overman; Benjamin Q. Roberts (Journal of Environmental Radioactivity, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Surfing the tidal wave: Use of transiently aquatic habitat by juvenile Pacific salmon and other fishes in estuaries - Daniel J. Scurfield; Phoebe L. Gross; Julian C. L. Gan; Jonathan W. Moore (Ecology, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

A conceptual analytical framework for green infrastructure (GI) towards resilience building in urban contexts: A Stakeholders' collaboration perspective - Frances Ifeoma Ukonze; Antoni B. Moore; Greg H. Leonard; Ben K. Daniel (Urban Climate, 2025)

Corrigendum to “Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes” [Biol. Conserv. 300 (2024), 110843] - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2025)

Drone-based infrared thermography to measure the intranasal temperature of baleen whales - Gina L. Lonati; Natasha Hynes; Halyna Klymentieva; Amy Warren; Daniel Zitterbart; Sebastian Richter; Michael J. Moore; Kimberley T. A. Davies (International Journal of Remote Sensing, 2025)

Comparing freshwater mussel responses to stress using life-history and Dynamic Energy Budget theory - Ines Haberle; Adrian P. Moore; Valery E. Forbes; Richard A. Brain; Daniel J. Hornbach; Nika Galic; Maxime Vaugeois (Science of The Total Environment, 2025)

Establishing the limitations on using archived marine mammal samples for stable isotope analysis: an examination of differing preservation methods on tissues of harbor porpoise ( Phocoena phocoena ) and gray seal ( Halichoerus grypus ) - Daniel M. Moore; Emily G. Cunningham; Kayla D. Crowder; Darren R. Gröcke (Marine Mammal Science, 2025)
The use of biological samples from museum and/or archive collections is common in stable isotope research, particularly for marine mammals. Yet, the temporal stability of isotopic values across various tissue types and the influence of different preservatives on these values are not fully understood, posing significant challenges for accurate data interpretation. Here we examine the impact of three different tissue preservation methods (DMSO, ethanol, freezing), on seven different tissues (blubber, heart, kidney, lung, liver, muscle, and skin) from both a harbor porpoise ( Phocoena phocoena ) and a gray seal ( Halichoerus grypus ) for stable isotope analysis in a 1‐year period. Our results demonstrate that storage in DMSO generates greater temporal variability in δ 13 C and δ 15 N for all tissue types, particularly in the first six months of storage. Furthermore, tissues stored in DMSO often exhibited lower δ13C and δ15N values compared to those stored frozen or in ethanol. This finding highlights a significant issue for studies utilizing tissues stored in DMSO, regardless of the storage duration. These results underscore the critical need for careful consideration of preservation methods in studies involving stored tissues, providing valuable insights for experimental design and management of tissue archives.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Measuring the association between the opening of a new multi-national restaurant with young people's eating behaviours - Helen J. Moore; Claire L. O'Malley; Scott Lloyd; Fatemeh Eskandari; Kelly Rose; Mark Butler; Tim G. Townshend; Heather Brown; Daniel Clarkson; Amelia A. Lake (Appetite, 2024)

Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2024)

Incidence of contrast-induced neurotoxicity following endovascular treatment of unruptured intracranial aneurysms: a single-centre cohort study - Frederick P. Mariajoseph; Leon T. Lai; Justin Moore; Ronil V. Chandra; Tony Goldschlager; Adrian Praeger; Daniel Yu; Lee-Anne Slater (Acta Neurologica Belgica, 2024)
Background Contrast-induced neurotoxicity (CIN) is a recognised complication of endovascular procedures and has been increasingly observed in recent years. Amongst other clinical gaps, the precise incidence of CIN is unclear, particularly following intracranial interventional procedures. Methods A retrospective study of consecutive patients undergoing elective endovascular treatment of unruptured intracranial aneurysms (UIAs) was performed. Patients with previously ruptured aneurysms were excluded. The primary aim of this study was to determine the incidence of CIN following endovascular UIA treatment. Our secondary aim was to isolate potential predictive factors for developing CIN. Results From 2017 to 2023, a total of 158 patients underwent endovascular UIA treatment, with a median age of 64 years (IQR: 54–72), and 70.3% of female sex. Over the study period, the crude incidence of CIN was 2.5% (95% CI: 0.7 – 6.4%). The most common clinical manifestation of CIN was confusion (75%) and seizures (50%). Statistical analysis was conducted, and prolonged procedural duration was found be significantly associated with developing CIN (OR 12.55; p = 0.030). Conclusion Clinicians should be aware of the risk of CIN following endovascular neurointervention, particularly following technically challenging cases resulting in prolonged procedural time.

Straight from the horse's mouth: The effect of different feedstuffs on oral pH in horses and ponies - S.P. Daniels; E.J. Whiteside; S. Martin; M.J.S. Moore-Colyer; P. Harris (Journal of Equine Veterinary Science, 2024)

Soil solution chemistry weak response to long-term N addition points towards a strong resilience of northeastern American forests to past and future N deposition - Daniel Houle; Marie Renaudin; Louis Duchesne; Jean-David Moore; Apolline Benoist (Science of The Total Environment, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Beneficial ‘inefficiencies’ of western ranching: Flood-irrigated hay production sustains wetland systems by mimicking historic hydrologic processes - J. Patrick Donnelly; Kelsey Jensco; John S. Kimball; Johnnie N. Moore; David Ketchum; Daniel P. Collins; David E. Naugle (Agriculture, Ecosystems & Environment, 2024)

Characterizing sulfur redox state and geochemical implications in deep-time using mineral chemistry network analysis - Eli K. Moore; Joseph E. Diedolf; Shaunna M. Morrison; Daniel R. Hummer (Geochimica et Cosmochimica Acta, 2024)

Evidence of heat sensitivity in people with Parkinson’s disease - Andrew P. Hunt; Aline Souza Pagnussat; Alexander Lehn; Daniel Moore; Daniel Schweitzer; E-Liisa Laakso; Ewald Hennig; Meg E. Morris; Graham Kerr; Ian Stewart (International Journal of Biometeorology, 2024)
Examining how heat affects people with Parkinson’s disease is essential for informing clinical decision-making, safety, well-being, and healthcare planning. While there is evidence that the neuropathology associated with Parkinson’s disease affects thermoregulatory mechanisms, little attention has been given to the association of heat sensitivity to worsening symptoms and restricted daily activities in people with this progressive disease. Using a cross-sectional study design, we examined the experiences of people diagnosed with Parkinson’s disease in the heat. Two-hundred and forty-seven people completed an online survey (age: 66.0 ± 9.2 years; sex: male = 102 (41.3%), female = 145 (58.7%)), of which 195 (78.9%) reported becoming more sensitive to heat with Parkinson’s disease. Motor and nonmotor symptoms worsened with heat in 182 (73.7%) and 203 (82.2%) respondents, respectively. The most commonly reported symptoms to worsen included walking difficulties, balance impairment, stiffness, tremor, fatigue, sleep disturbances, excess sweating, difficulty concentrating, and light-headedness when standing. Concerningly, over half indicated an inability to work effectively in the heat, and nearly half reported that heat impacted their ability to perform household tasks and social activities. Overall, heat sensitivity was common in people with Parkinson’s disease and had a significant impact on symptomology, day-to-day activities and quality of life.

SEMWISE: A national soil health scoring framework for agricultural systems - Heather L. Deel; Jennifer M. Moore; Daniel K. Manter (Applied Soil Ecology, 2024)

Associations between urban greenspace and depressive symptoms in Mexico's cities using different greenspace metrics - Maryia Bakhtsiyarava; Yang Ju; Mika Moran; Daniel A. Rodríguez; Iryna Dronova; Xavier Delclòs-Alió; Kari Moore; Marianela Castillo-Riquelme; Cecilia Anza-Ramirez (Applied Geography, 2024)

Optimizing process flow diagrams to guide implementation of a colorectal cancer screening intervention in new settings - Meghan C. O’Leary; Kristen Hassmiller Lich; Daniel S. Reuland; Alison T. Brenner; Alexis A. Moore; Shana Ratner; Sarah A. Birken; Stephanie B. Wheeler (Cancer Causes & Control, 2023)
Purpose The goal of this study was to assess acceptability of using process flow diagrams (or process maps) depicting a previously implemented evidence-based intervention (EBI) to inform the implementation of similar interventions in new settings. Methods We developed three different versions of process maps, each visualizing the implementation of the same multicomponent colorectal cancer (CRC) screening EBI in community health centers but including varying levels of detail about how it was implemented. Interviews with community health professionals and practitioners at other sites not affiliated with this intervention were conducted. We assessed their preferences related to the map designs, their potential utility for guiding EBI implementation, and the feasibility of implementing a similar intervention in their local setting given the information available in the process maps. Results Eleven community health representatives were interviewed. Participants were able to understand how the intervention was implemented and engage in discussions around the feasibility of implementing this type of complex intervention in their local system. Potential uses of the maps for supporting implementation included staff training, role delineation, monitoring and quality control, and adapting the components and implementation activities of the existing intervention. Conclusion Process maps can potentially support decision-making about the adoption, implementation, and adaptation of existing EBIs in new contexts. Given the complexities involved in deciding whether and how to implement EBIs, these diagrams serve as visual, easily understood tools to inform potential future adopters of the EBI about the activities, resources, and staffing needed for implementation.

Uptake of colorectal cancer screening after mailed fecal immunochemical test (FIT) outreach in a newly eligible 45–49-year-old community health center population - Meghan C. O’Leary; Daniel S. Reuland; Sara Y. Correa; Alexis A. Moore; Teri L. Malo; Xianming Tan; Catherine L. Rohweder; Stephanie B. Wheeler; Alison T. Brenner (Cancer Causes & Control, 2023)
Purpose We assessed fecal immunochemical test (FIT) uptake following a mailed FIT intervention among 45–49-year-olds newly eligible for colorectal cancer (CRC) screening based on 2021 United States Preventive Services Task Force screening recommendations. We also tested the effect of an enhanced versus plain mailing envelope on FIT uptake. Methods In February 2022 we mailed FITs to eligible 45–49-year-olds at one Federally Qualified Health Center (FQHC) clinic. We determined the proportion who completed FITs within 60 days. We also conducted a nested randomized trial comparing uptake using an enhanced envelope (padded with tracking label and colored messaging sticker) versus plain envelope. Finally, we determined the change in CRC screening by any modality (e.g., FIT, colonoscopy) among all clinic patients in this age group (i.e., clinic-level screening) between baseline and 6 months post-intervention. Results We mailed FITs to 316 patients. Sample characteristics: 57% female, 58% non-Hispanic Black, and 50% commercially insured. Overall, 54/316 (17.1%) returned a FIT within 60 days, including 34/158 (21.5%) patients in the enhanced envelope arm versus 20/158 (12.7%) in the plain envelope arm (difference 8.9 percentage points, 95% CI: 0.6–17.2). Clinic-level screening among all 45–49-year-olds increased 16.6 percentage points (95% CI: 10.9–22.3), from 26.7% at baseline to 43.3% at 6 months. Conclusion CRC screening appeared to increase following a mailed FIT intervention among diverse FQHC patients aged 45–49. Larger studies are needed to assess acceptability and completion of CRC screening in this younger population. Visually appealing mailers may improve uptake when implementing mailed interventions. Trial registration The trial was registered on May 28, 2020 at ClinicalTrials.gov (identifier NCT04406714).

Complex temperature mosaics across space and time in estuaries: implications for current and future nursery function for Pacific salmon - Phoebe L. Gross; Julian C.L. Gan; Daniel J. Scurfield; Cory Frank; Cedar Frank; Caelan McLean; Chris Bob; Jonathan W. Moore (Frontiers in Marine Science, 2023)
Water temperature is a key dimension of estuaries that can influence important biological processes including organismal growth, survival, and habitat use. For example, juvenile Pacific salmon rely on temperature-mediated growth opportunities in estuaries during seaward migration in the spring and summer. However, oncoming climate change is warming estuary temperatures and transforming growth potential. Yet, it is likely that estuary water temperatures are complex and dynamic across space and time. Here we investigated spatial and temporal patterns of water temperature across two contrasting estuaries on Vancouver Island, BC, and used these data to simulate juvenile Chinook salmon growth potential under both present conditions and a simplified scenario of climate warming. Summer temperatures were warmer and more spatially homogeneous across the Englishman River estuary relative to the Salmon River estuary. Within each system, temperature was variable across habitats and sites, appearing to be driven by a combination of local climate, river and ocean temperatures, tidal fluctuations, and habitat features. This shifting mosaic of temperatures generated a complex portfolio of growth opportunities for juvenile Chinook salmon. There were broad patterns of increasing growth potential across both systems as temperatures warmed in early summer. However, excessively hot late summer temperatures drove steep declines in growth potential across the Englishman River estuary, while positive trends continued through August in the Salmon River estuary. A simple climate change scenario revealed that estuaries and habitats may have differing vulnerabilities to increasing temperatures—with climate warming, favorable growth opportunities were even more constricted to early summer in the Englishman River estuary, but expanded across most habitats and times in the Salmon River estuary given lower baseline temperatures and higher habitat complexity. Collectively, this work underscores the importance of habitat complexity and local climate for maintaining diverse growth opportunities across estuaries, which may confer resilience to the nursery function of estuaries as temperature mosaics warm.

Wild salmon enumeration and monitoring using deep learning empowered detection and tracking - William I. Atlas; Sami Ma; Yi Ching Chou; Katrina Connors; Daniel Scurfield; Brandon Nam; Xiaoqiang Ma; Mark Cleveland; Janvier Doire; Jonathan W. Moore; Ryan Shea; Jiangchuan Liu (Frontiers in Marine Science, 2023)
Pacific salmon have experienced declining abundance and unpredictable returns, yet remain vital to livelihoods, food security, and cultures of coastal communities around the Pacific Rim, creating a need for reliable and timely monitoring to inform sustainable fishery management. Currently, spawning salmon abundance is often monitored with in-river video or sonar cameras. However, reviewing video for estimates of salmon abundance from these programs requires thousands of hours of staff time, and data are typically not available until after the fishing season is completed. Computer vision deep learning can enable rapid and reliable processing of data, with potentially transformative applications in salmon population assessment and fishery management. Working with two First Nations fishery programs in British Columbia, Canada, we developed, trained, and tested deep learning models to perform object detection and multi-object tracking for automated video enumeration of salmon passing two First Nation-run weirs. We gathered and annotated more than 500,000 frames of video data encompassing 12 species, including seven species of anadromous salmonids, and trained models for multi-object tracking and species detection. Our top performing model achieved a mean average precision (mAP) of 67.6%, and species-specific mAP scores > 90% for coho and > 80% for sockeye salmon when trained with a combined dataset of Kitwanga and Bear Rivers’ salmon annotations. We also tested and deployed a prototype for a real-time monitoring system that can perform computer vision deep learning analyses on site. Computer vision models and off-grid monitoring systems show promise for automated counting and species identification. A key future priority will be working with stewardship practitioners and fishery managers to apply salmon computer vision, testing and applying edge-capable computing solutions for in-situ analysis at remote sites, and developing tools for independent user-led computer vision analysis by non-computer scientists. These efforts can advance in-season monitoring and decision making to support adaptive management of sustainable wild salmon fisheries.

OME-Zarr: a cloud-optimized bioimaging file format with international community support - Josh Moore; Daniela Basurto-Lozada; Sébastien Besson; John Bogovic; Jordão Bragantini; Eva M. Brown; Jean-Marie Burel; Xavier Casas Moreno; Gustavo de Medeiros; Erin E. Diel; David Gault; Satrajit S. Ghosh; et al. (Histochemistry and Cell Biology, 2023)
A growing community is constructing a next-generation file format (NGFF) for bioimaging to overcome problems of scalability and heterogeneity. Organized by the Open Microscopy Environment (OME), individuals and institutes across diverse modalities facing these problems have designed a format specification process (OME-NGFF) to address these needs. This paper brings together a wide range of those community members to describe the cloud-optimized format itself—OME-Zarr—along with tools and data resources available today to increase FAIR access and remove barriers in the scientific process. The current momentum offers an opportunity to unify a key component of the bioimaging domain—the file format that underlies so many personal, institutional, and global data management and analysis tasks.

Circulating Plasma miRNA Homologs in Mice and Humans Reflect Familial Cerebral Cavernous Malformation Disease - Sharbel G. Romanos; Abhinav Srinath; Ying Li; Bingqing Xie; Chang Chen; Yan Li; Thomas Moore; Dehua Bi; Je Yeong Sone; Rhonda Lightle; Nick Hobson; Dongdong Zhang; et al. (Translational Stroke Research, 2023)

Rapid prototyping for quantifying belief weights of competing hypotheses about emergent diseases - Ellen P. Robertson; Daniel P. Walsh; Julien Martin; Thierry M. Work; Christina A. Kellogg; James S. Evans; Victoria Barker; Aine Hawthorn; Greta Aeby; Valerie J. Paul; Brian K. Walker; Yasunari Kiryu; et al. (Journal of Environmental Management, 2023)

Stationary and drone-assisted methane plume localization with dispersion spectroscopy - Michael G. Soskind; Nathan P. Li; Daniel P. Moore; Yifeng Chen; Lars P. Wendt; James McSpiritt; Mark A. Zondlo; Gerard Wysocki (Remote Sensing of Environment, 2023)

Chemistry of soil and foliage in declining sugar maple stands over 13 years of nitrogen addition - Jean-David Moore; Daniel Houle (Forest Ecology and Management, 2023)

Ecological carrying capacity in mariculture: Consideration and application in geographic strategies and policy - Jeffrey Fisher; Dror Angel; Myriam Callier; Daniel Cheney; Ramon Filgueira; Bobbi Hudson; Christopher W. McKindsey; Lisa Milke; Heather Moore; Francis O’Beirn; Jack O’Carroll; Berit Rabe; et al. (Marine Policy, 2023)

The influence of oxygen and electronegativity on iron mineral chemistry throughout Earth’s history - Eli K. Moore; Alex Ostroverkhova; Daniel Hummer; Shaunna Morrison; Yarissa Peralta; Stephanie J. Spielman (Precambrian Research, 2023)

Offsetting environmental impacts beyond climate change: the Circular Ecosystem Compensation approach - Daniel Moore; Vanessa Bach; Matthias Finkbeiner; Theresa Honkomp; Heinz Ahn; Madlen Sprenger; Linda Froese; Dirk Gratzel (Journal of Environmental Management, 2023)

Challenges for environmental governance: policy issue interdependencies might not lead to collaboration - Johanna Hedlund; Daniel Nohrstedt; Tiffany Morrison; Michele-Lee Moore; Örjan Bodin (Sustainability Science, 2023)
Policy actors address complex environmental problems by engaging in multiple and often interdependent policy issues. Policy issue interdependencies imply that efforts by actors to address separate policy issues can either reinforce (‘win–win’) or counteract (‘trade-off’) each other. Thus, if interdependent issues are managed in isolation instead of being coordinated, the most effective and well-balanced solution to the underlying problem might never be realised. This study asks if reinforcing and counteracting interdependencies have different impacts on perception and collaboration. Our empirical study of collaborative water governance in the Norrström basin, Sweden, shows that policy actors often avoid collaborating when the policy issues exhibit reinforcing interdependencies. Our evidence indicates a perceived infeasibility of acting on reinforcing interdependencies. We also find that actors do not consider counteracting interdependencies (‘trade-offs’) at all when they engage in collaboration. Further, even though actors were aware of counteracting and reinforcing interdependencies, our analyses suggest they might be less aware of the former. These findings illustrate that actors either avoid each other due to policy issue interdependencies or, at best, ignore existing interdependencies when engaging in collaboration. Our study highlights the importance of problem perception in accomplishing integrated solutions to complex environmental problems, and of how understandings of different types of interdependencies shape collaboration in environmental governance.

Passive Treatment of Circumneutral Mine Drainage from the St. Louis Mine Tunnel, Rico CO: Part 2—Vertical Biotreatment Train Pilot Study - Daniel M. Dean; James R. Fricke; Arthur C. Riese; Terry J. Moore; Anthony R. Brown (Mine Water and the Environment, 2022)
This is the second of three papers dealing with metal-bearing circumneutral mine drainage from the inactive Rico-Argentine mine site located at an elevation of ≈ 2740 m (9000 feet) in the San Juan mountain range in southwestern Colorado. This paper evaluates two years of mine drainage treatment using a passive system that included a vertical-flow engineered biotreatment cell. The collapsed St. Louis Tunnel (SLT) discharges circumneutral mine water from several sources that contains elevated concentrations of Cd, Cu, Fe, Mn, Zn. A demonstration-scale 114 L/min (30 gpm) gravity-flow passive treatment system was installed, consisting of a settling basin (utilizing coagulant addition to improve suspended solids settling efficiency), an anaerobic sulfate-reducing bioreactor, and an aeration cascade for effluent polishing. The treatment system generally met target treatment goals for Cd, Cu, Fe, and Pb. Nanophase ZnS in system effluent decreased the frequency of meeting total Zn project treatment goals. Unexpectedly high levels of Mn removal were observed in both the anaerobic bioreactor and the aeration cascade. Large seasonal variations in influent metals concentrations and pH present the greatest challenge in managing system performance.

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Predictive value of common genetic variants in idiopathic pulmonary fibrosis survival - Patrícia Caetano Mota; Miguel Luz Soares; Carlos Daniel Vasconcelos; António Carlos Ferreira; Bruno A. Lima; Elisabetta Manduchi; Jason H. Moore; Natália Melo; Hélder Novais-Bastos; José Miguel Pereira; Susana Guimarães; Conceição Souto Moura; et al. (Journal of Molecular Medicine, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Correction to: Pterocarpus marsupium extract extends replicative lifespan in budding yeast - Mitchell B. Lee; Michael G. Kiflezghi; Mitsuhiro Tsuchiya; Brian Wasko; Daniel T. Carr; Priya A. Uppal; Katherine A. Grayden; Yordanos C. Elala; Tu Anh Nguyen; Jesse Wang; Priya Rastogi; Sunny Nguyen; et al. (GeroScience, 2022)

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

The Open-Ocean Gulf of Mexico After Deepwater Horizon: Synthesis of a Decade of Research - Tracey T. Sutton; Rosanna J. Milligan; Kendra Daly; Kevin M. Boswell; April B. Cook; Maëlle Cornic; Tamara Frank; Kaitlin Frasier; Daniel Hahn; Frank Hernandez; John Hildebrand; Chuanmin Hu; et al. (Frontiers in Marine Science, 2022)
The scale of the Deepwater Horizon disaster was and is unprecedented: geographic extent, pollutant amount, countermeasure scope, and of most relevance to this Research Topic issue, range of ecotypes affected. These ecotypes include coastal/nearshore, continental shelf, deep benthic, and open-ocean domains, the last of which is the subject of this synthesis. The open-ocean ecotype comprises ~90% of the volume of the Gulf of Mexico. The exact percentage of this ecotype contaminated with toxins is unknown due to its three-dimensional nature and dynamics, but estimates suggest that the footprint encompassed most of its eastern half. Further, interactions between the water column and the deep benthos may be persistent, making this synthesis one of time (a decade) rather than event conclusion. Here we examine key elements of the open-ocean ecosystem, with emphasis on vulnerability and resilience. Of paramount importance relative to the Gulf nearshore and shelf ecotypes, pre-disaster baseline data were lacking for most of the fauna. In such cases, inferences were drawn from post-disaster assessments. Both phytoplankton and mesozooplankton vulnerabilities were quite high, but resilience appeared equally so. The phytoplankton situation was a bit more complex in that toxin-imposed reductions may have been offset by nutrient injection via high freshwater discharge in 2010. Intermediate trophic levels exhibited population-level depressions, ostensibly due to high vulnerability and low resilience. Apex predator impacts were variable. Certain large epipelagic fishes may have avoided the highest concentrations of hydrocarbons/dispersant, and thus larval abundances returned to pre-disaster levels of variability and abundance within a few years after a steep initial decline. Oceanic cetaceans, particularly shallow-diving stenellid dolphins, did not appear to avoid oiled waters and exhibited strong declines in the northern Gulf. Given that population declines of many open-ocean taxa appear to be ongoing a decade later, we conclude that this largest of Gulf ecosystem components, like its deep-benthic counterpart, is as fragile as it is voluminous. This is particularly concerning given the rapid, and likely irreversible, shift to deeper waters by the US and Mexican oil industries in concert with the higher likelihood of accidents with increasing platform depth.

Cover and density of southwestern ponderosa pine understory plants in permanent chart quadrats (2002–2020) - Margaret M. Moore; Jeffrey S. Jenness; Daniel C. Laughlin; Robert T. Strahan; Jonathan D. Bakker; Helen E. Dowling; Judith D. Springer (Ecology, 2022)
This data set consists of 101 permanent 1 m × 1 m (1‐m 2 ) quadrats located within southwestern ponderosa pine ecosystems near Flagstaff, Arizona, USA. Individual plants in these quadrats were identified and mapped annually for 19 years (2002–2020). The original chart quadrats were established between 1912 and 1927 to determine the effects of domestic livestock grazing on herbaceous plants and pine seedlings. Today these data provide opportunities to examine the effects of climate and land‐use change on plant demography, population dynamics, and community processes. We provide the following data and data formats: (1) digitized maps of all plant locations in shapefile and geodatabase format, (2) shapefiles showing annual locations of each individual plant species, (3) annual maps of each quadrat in TIFF and PDF format, (4) annual basal area of each species per quadrat for species mapped as polygons, (5) tabular representation of polygon areas and centroid locations for plant species mapped as polygons, (6) tabular representation of point locations for plant species mapped as points, (7) plot‐scale 20 m × 20 m overstory tree canopy cover, tree basal area, parent material, and elevation, (8) quadrat‐scale information (e.g., quadrat site and number, coordinates in UTM Zone 12 and latitude/longitude, and descriptive comments for each quadrat), (9) plant species list, (10) summary of plant species observed in each quadrat, (11) summary of quadrats mapped by site and year, and (12) data formatted for use in Integral Projection Models (IPM) and plant population analyses. There are no copyright restrictions; please cite this paper and the associated data set when data are used in publications.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Addressing the welfare needs of farmed lumpfish: Knowledge gaps, challenges and solutions - Carlos Garcia de Leaniz; Carolina Gutierrez Rabadan; Sara I. Barrento; Rebecca Stringwell; Paul N. Howes; Ben A. Whittaker; Jessica F. Minett; Robert G. Smith; Craig L. Pooley; Ben J. Overland; Leigh Biddiscombe; Richard Lloyd; et al. (Reviews in Aquaculture, 2022)
Lumpfish ( Cyclopterus lumpus L.) are increasingly being used as cleaner fish to control parasitic sea lice, one of the most important threats to salmon farming. However, lumpfish cannot survive feeding solely on sea lice, and their mortality in salmon net‐pens can be high, which has welfare, ethical and economic implications. The industry is under increasing pressure to improve the welfare of lumpfish, but little guidance exists on how this can be achieved. We undertook a knowledge gap and prioritisation exercise using a Delphi approach with participants from the fish farming sector, animal welfare, academia and regulators to assess consensus on the main challenges and potential solutions for improving lumpfish welfare. Consensus among participants on the utility of 5 behavioural and 12 physical welfare indicators was high (87–89%), reliable (Cronbach's alpha = 0.79, 95CI = 0.69–0.92) and independent of participant background. Participants highlighted fin erosion and body damage as the most useful and practical operational welfare indicators, and blood parameters and behavioural indicators as the least practical. Species profiling revealed profound differences between Atlantic salmon and lumpfish in relation to behaviour, habitat preferences, nutritional needs and response to stress, suggesting that applying a common set of welfare standards to both species cohabiting in salmon net‐pens may not work well for lumpfish. Our study offers 16 practical solutions for improving the welfare of lumpfish and illustrates the merits of the Delphi approach for achieving consensus among stakeholders on welfare needs, targeting research where is most needed and generating workable solutions.

Pterocarpus marsupium extract extends replicative lifespan in budding yeast - Mitchell B. Lee; Michael G. Kiflezghi; Mitsuhiro Tsuchiya; Brian Wasko; Daniel T. Carr; Priya A. Uppal; Katherine A. Grayden; Yordanos C. Elala; Tu Anh Nguyen; Jesse Wang; Priya Ragosti; Sunny Nguyen; et al. (GeroScience, 2021)

Population structure associated with bioregion and seasonal prey distribution for Indo‐Pacific bottlenose dolphins ( Tursiops aduncus ) in South Africa - O. Alejandra Vargas‐Fonseca; Paige Yates; Stephan P. Kirkman; Pierre A. Pistorius; Daniel M. Moore; Ada Natoli; Victor Cockcroft; A. Rus Hoelzel (Molecular Ecology, 2021)
Many marine species exhibit fine‐scale population structure despite high mobility and a lack of physical barriers to dispersal, but the evolutionary drivers of differentiation in these systems are generally poorly understood. Here we investigate the potential role of habitat transitions and seasonal prey distributions on the evolution of population structure in the Indo‐Pacific bottlenose dolphin, Tursiops aduncus , off South Africa's coast, using double‐digest restriction‐site associated DNA sequencing. Population structure was identified between the eastern and southern coasts and correlated with the habitat transition between the temperate Agulhas (southern) and subtropical Natal (eastern) Bioregions, suggesting differentiation driven by resource specializations. Differentiation along the Natal coast was comparatively weak, but was evident in some analyses and varied depending on whether the samples were collected during or outside the seasonal sardine ( Sardinops sagax ) run. This local abundance of prey could influence the ranging patterns and apparent genetic structure of T. aduncus . These findings have significant and transferable management implications, most importantly in terms of differentiating populations inhabiting distinct bioregions and seasonal structural patterns within a region associated with the movement of prey resources.

Fine root dynamics across pantropical rainforest ecosystems - Walter Huaraca Huasco; Terhi Riutta; Cécile A. J. Girardin; Fernando Hancco Pacha; Beisit L. Puma Vilca; Sam Moore; Sami W. Rifai; Jhon del Aguila‐Pasquel; Alejandro Araujo Murakami; Renata Freitag; Alexandra C. Morel; Sheleme Demissie; et al. (Global Change Biology, 2021)
Fine roots constitute a significant component of the net primary productivity (NPP) of forest ecosystems but are much less studied than aboveground NPP. Comparisons across sites and regions are also hampered by inconsistent methodologies, especially in tropical areas. Here, we present a novel dataset of fine root biomass, productivity, residence time, and allocation in tropical old‐growth rainforest sites worldwide, measured using consistent methods, and examine how these variables are related to consistently determined soil and climatic characteristics. Our pantropical dataset spans intensive monitoring plots in lowland (wet, semi‐deciduous, and deciduous) and montane tropical forests in South America, Africa, and Southeast Asia ( n = 47). Large spatial variation in fine root dynamics was observed across montane and lowland forest types. In lowland forests, we found a strong positive linear relationship between fine root productivity and sand content, this relationship was even stronger when we considered the fractional allocation of total NPP to fine roots, demonstrating that understanding allocation adds explanatory power to understanding fine root productivity and total NPP. Fine root residence time was a function of multiple factors: soil sand content, soil pH, and maximum water deficit, with longest residence times in acidic, sandy, and water‐stressed soils. In tropical montane forests, on the other hand, a different set of relationships prevailed, highlighting the very different nature of montane and lowland forest biomes. Root productivity was a strong positive linear function of mean annual temperature, root residence time was a strong positive function of soil nitrogen content in montane forests, and lastly decreasing soil P content increased allocation of productivity to fine roots. In contrast to the lowlands, environmental conditions were a better predictor for fine root productivity than for fractional allocation of total NPP to fine roots, suggesting that root productivity is a particularly strong driver of NPP allocation in tropical mountain regions.

Roundup negatively impacts the behavior and nerve function of the Madagascar hissing cockroach (Gromphadorhina portentosa) - Megha Kanabar; Samuel Bauer; Zimuzo M. Ezedum; Ian P. Dwyer; William S. Moore; Gabriella Rodriguez; Aditya Mall; Anne T. Littleton; Michael Yudell; Jenil Kanabar; Wade J. Tucker; Emily R. Daniels; et al. (Environmental Science and Pollution Research, 2021)

Elevated levels of sulfur, nitrogen, and fluoride in small coastal streams near an aluminum smelter in north coastal British Columbia: a reply - R. Paul Weidman; Timothy J. Maguire; Jonathan W. Moore; Scott O. C. Mundle; Daniel T. Selbie (Environmental Monitoring and Assessment, 2021)

Vascular plant extinction in the continental United States and Canada - Wesley M. Knapp; Anne Frances; Reed Noss; Robert F. C. Naczi; Alan Weakley; George D. Gann; Bruce G. Baldwin; James Miller; Patrick McIntyre; Brent D. Mishler; Gerry Moore; Richard G. Olmstead; et al. (Conservation Biology, 2021)
Extinction rates are expected to increase during the Anthropocene. Current extinction rates of plants and many animals remain unknown. We quantified extinctions among the vascular flora of the continental United States and Canada since European settlement. We compiled data on apparently extinct species by querying plant conservation databases, searching the literature, and vetting the resulting list with botanical experts. Because taxonomic opinion varies widely, we developed an index of taxonomic uncertainty (ITU). The ITU ranges from A to F, with A indicating unanimous taxonomic recognition and F indicating taxonomic recognition by only a single author. The ITU allowed us to rigorously evaluate extinction rates. Our data suggest that 51 species and 14 infraspecific taxa, representing 33 families and 49 genera of vascular plants, have become extinct in our study area since European settlement. Seven of these taxa exist in cultivation but are extinct in the wild. Most extinctions occurred in the west, but this outcome may reflect the timing of botanical exploration relative to settlement. Sixty‐four percent of extinct plants were single‐site endemics, and many occurred outside recognized biodiversity hotspots. Given the paucity of plant surveys in many areas, particularly prior to European settlement, the actual extinction rate of vascular plants is undoubtedly much higher than indicated here.

Role of Sea Surface Microlayer Properties in Cloud Formation - Brianna N. Hendrickson; Sarah D. Brooks; Daniel C. O. Thornton; Richard H. Moore; Ewan Crosbie; Luke D. Ziemba; Craig A. Carlson; Nicholas Baetge; Jessica A. Mirrielees; Alyssa N. Alsante (Frontiers in Marine Science, 2021)
To date, the relative contribution of primary marine organic matter to the subset of atmospheric particles that nucleate cloud droplets is highly uncertain. Here, cloud condensation nuclei (CCN) measurements were conducted on aerosolized sea surface microlayer (SML) samples collected from the North Atlantic Ocean during the NASA North Atlantic Aerosols and Marine Ecosystems Study (NAAMES), κ values were predicted for three representative high molecular weight (HMW) organic components of marine aerosol: 6-glucose, humic acid, and ribulose-1,5-bisphosphate carboxylase/oxygenase (RuBisCO). The predicted κ values for pure organic aerosols varied by only ±0.01 across all of the organics chosen. For the desalted SML samples, calculations assuming an organic composition of entirely RuBisCO provided the closest predicted κ values for the desalted SML samples with a mean κ value of 0.53 ± 0.10. These results indicate that it is the sea salt in the SML which drives the cloud formation potential of marine aerosols. While the presence of organic material from the ocean surface waters may increase aerosol mass due to enrichment processes, cloud formation potential of mixed organic/salt primary marine aerosols will be slightly weakened or unchanged compared to sea spray aerosol.

The role of conidia in the dispersal of Ascochyta rabiei - Ihsanul Khaliq; Joshua Fanning; Paul Melloy; Jean Galloway; Kevin Moore; Daniel Burrell; Adam H. Sparks (European Journal of Plant Pathology, 2020)

Respiration cycle duration and seawater flux through open blowholes of humpback ( Megaptera novaeangliae ) and North Atlantic right ( Eubalaena glacialis ) whales - Maria Clara Iruzun Martins; Carolyn Miller; Phillip Hamilton; Jooke Robbins; Daniel P. Zitterbart; Michael Moore (Marine Mammal Science, 2020)
Little is known about the dynamics of baleen whale respiratory cycles, especially the mechanics and activity of the blowholes and their interaction with seawater. In this study, the duration of complete respiration cycles (expiration/inhalation events) were quantified for the first time in two species: North Atlantic right whale (NARW) and humpback whale (HW) using high resolution, detailed imagery from an unoccupied aerial system (UAS). The mean duration of complete respiration cycles (expiration/inhalation event) in the NARW and HW were 3.07 s ( SD = 0.503, n = 15) and 2.85 s ( SD = 0.581, n = 21), respectively. Furthermore, we saw no significant differences in respiration cycle duration between age and sex classes in the NARW, but significant differences were observed between age classes in the HW. The observation of seawater covering an open blowhole was also quantified, with NARW having 20% of all breaths with seawater presence versus 90% in HW. Seawater incursion has not been described previously and challenges the general consensus that water does not enter the respiratory tract in baleen whales. Prevalent seawater has implications for the analysis and interpretation of exhaled respiratory vapor/mucosa samples, as well as for the potential inhalation of oil in spills.

Impacts of industrial atmospheric emissions on watershed export of dissolved ions in coastal streams: a Bayesian modeling approach - Timothy J. Maguire; R. Paul Weidman; Scott O. C. Mundle; Jonathan W. Moore; Kyle A. Chezik; Daniel T. Selbie (Environmental Monitoring and Assessment, 2020)

Landscape and biophysical controls of lake productivity to inform evaluation of sockeye salmon ( Oncorhynchus nerka ) populations in data‐limited regions - William I. Atlas; Daniel T. Selbie; Carrie A. Holt; Steve Cox‐Rogers; Charmaine Carr‐Harris; Kara J. Pitman; Jonathan W. Moore (Limnology and Oceanography, 2020)
Landscape models are increasingly used to classify and predict the structure and productivity of data‐limited aquatic ecosystems. One such suite of ecosystems is on the remote North and Central Coast (NCC) of British Columbia, where sockeye salmon ( Oncorhynchus nerka ) rear in more than 150 lakes. Given their remoteness and limited resources for assessment, limnological and population monitoring in many of these lakes has been periodic or absent, limiting understanding of the status of populations and their habitats. Lake photosynthetic rate (PR) estimates are foundational to models of sockeye salmon nursery lake productive capacity. Using data from 61 lakes across the NCC, we compared a suite of landscape and lake variables in an information theoretic framework producing a set of models relating these characteristics to lake PR. A categorical variable related to lake biogeochemistry—whether a lake is humic stained, clear, or glacially turbid—was the most important variable predicting lake PR and was included in all models. Lake surface area relative to upstream catchment size and lake perimeter‐to‐surface‐area ratio were also important, with smaller upstream catchments yielding higher production, and high shoreline complexity correlated with lower productivity as measured by limnetic PR. Model‐averaged predictions of PR from the four models with the lowest residual error were created for 96 lakes currently lacking limnological assessments. These landscape models represent a valuable starting point for evaluating lake‐specific carrying capacities for data‐poor sockeye salmon populations under Canada's Wild Salmon Policy.

Southernmost distribution limit for endangered Peladillas ( Aplochiton taeniatus ) and non‐native coho salmon ( Oncorhynchus kisutch ) coexisting within the Cape Horn biosphere reserve, Chile - Alan Maldonado‐Márquez; Tamara Contador; Javier Rendoll‐Cárcamo; Sabrina Moore; Carolina Pérez‐Troncoso; Daniel Gomez‐Uchida; Chris Harrod (Journal of Fish Biology, 2020)
The Cape Horn Biosphere Reserve, one of the last wild areas of the planet, is not exempt from the pressures of global change, such as non‐native species introductions. During 2018 and 2019 we studied the Róbalo river basin in order to update the diversity and distribution of fishes. Here, we report for the first time the native and endangered “Peladillas” Aplochiton taeniatus and the non‐native coho salmon Oncorhynchus kisutch . The coexistence of native and non‐native fishes poses a challenge for the management and conservation of aquatic biota from the Cape Horn Biosphere Reserve.

The importance of naturally attenuated SARS‐CoV ‐2 in the fight against COVID ‐19 - Jean Armengaud; Agnès Delaunay‐Moisan; Jean‐Yves Thuret; Eelco van Anken; Diego Acosta‐Alvear; Tomás Aragón; Carolina Arias; Marc Blondel; Ineke Braakman; Jean‐François Collet; René Courcol; Antoine Danchin; et al. (Environmental Microbiology, 2020)
The current SARS‐CoV‐2 pandemic is wreaking havoc throughout the world and has rapidly become a global health emergency. A central question concerning COVID‐19 is why some individuals become sick and others not. Many have pointed already at variation in risk factors between individuals. However, the variable outcome of SARS‐CoV‐2 infections may, at least in part, be due also to differences between the viral subspecies with which individuals are infected. A more pertinent question is how we are to overcome the current pandemic. A vaccine against SARS‐CoV‐2 would offer significant relief, although vaccine developers have warned that design, testing and production of vaccines may take a year if not longer. Vaccines are based on a handful of different designs (i), but the earliest vaccines were based on the live, attenuated virus. As has been the case for other viruses during earlier pandemics, SARS‐CoV‐2 will mutate and may naturally attenuate over time (ii). What makes the current pandemic unique is that, thanks to state‐of‐the‐art nucleic acid sequencing technologies, we can follow in detail how SARS‐CoV‐2 evolves while it spreads. We argue that knowledge of naturally emerging attenuated SARS‐CoV‐2 variants across the globe should be of key interest in our fight against the pandemic.

Climate and human water use diminish wetland networks supporting continental waterbird migration - J. Patrick Donnelly; Sammy L. King; Nicholas L. Silverman; Daniel P. Collins; Eduardo M. Carrera‐Gonzalez; Alberto Lafón‐Terrazas; Johnnie N. Moore (Global Change Biology, 2020)
Migrating waterbirds moving between upper and lower latitudinal breeding and wintering grounds rely on a limited network of endorheic lakes and wetlands when crossing arid continental interiors. Recent drying of global endorheic water stores raises concerns over deteriorating migratory pathways, yet few studies have considered these effects at the scale of continental flyways. Here, we investigate the resiliency of waterbird migration networks across western North America by reconstructing long‐term patterns (1984–2018) of terminal lake and wetland surface water area in 26 endorheic watersheds. Findings were partitioned regionally by snowmelt‐ and monsoon‐driven hydrologies and combined with climate and human water‐use data to determine their importance in predicting surface water trends. Nonlinear patterns of lake and wetland drying were apparent along latitudinal flyway gradients. Pervasive surface water declines were prevalent in northern snowmelt watersheds (lakes −27%, wetlands −47%) while largely stable in monsoonal watersheds to the south (lakes −13%, wetlands +8%). Monsoonal watersheds represented a smaller proportion of total lake and wetland area, but their distribution and frequency of change within highly arid regions of the continental flyway increased their value to migratory waterbirds. Irrigated agriculture and increasing evaporative demands were the most important drivers of surface water declines. Underlying agricultural and wetland relationships however were more complex. Approximately 7% of irrigated lands linked to flood irrigation and water storage practices supported 61% of all wetland inundation in snowmelt watersheds. In monsoonal watersheds, small earthen dams, meant to capture surface runoff for livestock watering, were a major component of wetland resources (67%) that supported networks of isolated wetlands surrounding endorheic lakes. Ecological trends and human impacts identified herein underscore the importance of assessing flyway‐scale change as our model depictions likely reflect new and emerging bottlenecks to continental migration.

Belowground Biomass Response to Nutrient Enrichment Depends on Light Limitation Across Globally Distributed Grasslands - Elsa E. Cleland; Eric M. Lind; Nicole M. DeCrappeo; Elizabeth DeLorenze; Rachel Abbott Wilkins; Peter B. Adler; Jonathan D. Bakker; Cynthia S. Brown; Kendi F. Davies; Ellen Esch; Jennifer Firn; Scott Gressard; et al. (Ecosystems, 2019)

Current Status and Future Challenges of Weather Radar Polarimetry: Bridging the Gap between Radar Meteorology/Hydrology/Engineering and Numerical Weather Prediction - Guifu Zhang; Vivek N. Mahale; Bryan J. Putnam; Youcun Qi; Qing Cao; Andrew D. Byrd; Petar Bukovcic; Dusan S. Zrnic; Jidong Gao; Ming Xue; Youngsun Jung; Heather D. Reeves; et al. (Advances in Atmospheric Sciences, 2019)

Overexpressing ovotransferrin and avian β-defensin-3 improves antimicrobial capacity of chickens and poultry products - Caitlin A. Cooper; Mark L. Tizard; Tamsyn Stanborough; Sean C. Moore; P. Scott Chandry; Kristie A. Jenkins; Terry G. Wise; Terri E. O’Neil; Daniel S. Layton; Kirsten R. Morris; Robert J. Moore; Narelle Fegan; et al. (Transgenic Research, 2019)

Impact of Climate Change on Vibrio vulnificus Abundance and Exposure Risk - Reem Deeb; Daniel Tufford; Geoffrey I. Scott; Janet Gooch Moore; Kirstin Dow (Estuaries and Coasts, 2018)

Comparative genomics and physiology of the genus Methanohalophilus , a prevalent methanogen in hydraulically fractured shale - Mikayla A. Borton; Rebecca A. Daly; Bridget O'Banion; David W. Hoyt; Daniel N. Marcus; Susan Welch; Sybille S. Hastings; Tea Meulia; Richard A. Wolfe; Anne E. Booker; Shikha Sharma; David R. Cole; et al. (Environmental Microbiology, 2018)
Summary About 60% of natural gas production in the United States comes from hydraulic fracturing of unconventional reservoirs, such as shales or organic‐rich micrites. This process inoculates and enriches for halotolerant microorganisms in these reservoirs over time, resulting in a saline ecosystem that includes methane producing archaea. Here, we survey the biogeography of methanogens across unconventional reservoirs, and report that members of genus Methanohalophilus are recovered from every hydraulically fractured unconventional reservoir sampled by metagenomics. We provide the first genomic sequencing of three isolate genomes, as well as two metagenome assembled genomes (MAGs). Utilizing six other previously sequenced isolate genomes and MAGs, we perform comparative analysis of the 11 genomes representing this genus. This genomic investigation revealed distinctions between surface and subsurface derived genomes that are consistent with constraints encountered in each environment. Genotypic differences were also uncovered between isolate genomes recovered from the same well, suggesting niche partitioning among closely related strains. These genomic substrate utilization predictions were then confirmed by physiological investigation. Fine‐scale microdiversity was observed in CRISPR‐Cas systems of Methanohalophilus , with genomes from geographically distinct unconventional reservoirs sharing spacers targeting the same viral population. These findings have implications for augmentation strategies resulting in enhanced biogenic methane production in hydraulically fractured unconventional reservoirs.

Troubled waters: Threats and extinction risk of the sharks, rays and chimaeras of the Arabian Sea and adjacent waters - Rima W. Jabado; Peter M. Kyne; Riley A. Pollom; David A. Ebert; Colin A. Simpfendorfer; Gina M. Ralph; Shaikha S. Al Dhaheri; K. V. Akhilesh; Khadeeja Ali; Mohamud Hassan Ali; Tariq M. S. Al Mamari; K. K. Bineesh; et al. (Fish and Fisheries, 2018)
The extinction risk of sharks, rays and chimaeras is higher than that for most other vertebrates due to low intrinsic population growth rates of many species and the fishing intensity they face. The Arabian Sea and adjacent waters border some of the most important chondrichthyan fishing and trading nations globally, yet there has been no previous attempt to assess the conservation status of species occurring here. Using IUCN Red List of Threatened Species Categories and Criteria and their guidelines for application at the regional level, we present the first assessment of extinction risk for 153 species of sharks, rays and chimaeras. Results indicate that this region, home to 15% of described chondrichthyans including 30 endemic species, has some of the most threatened chondrichthyan populations in the world. Seventy‐eight species (50.9%) were assessed as threatened (Critically Endangered, Endangered or Vulnerable), and 27 species (17.6%) as Near Threatened. Twenty‐nine species (19%) were Data Deficient with insufficient information to assess their status. Chondrichthyan populations have significantly declined due to largely uncontrolled and unregulated fisheries combined with habitat degradation. Further, there is limited political will and national and regional capacities to assess, manage, conserve or rebuild stocks. Outside the few deepsea locations that are lightly exploited, the prognosis for the recovery of most species is poor in the near‐absence of management. Concerted national and regional management measures are urgently needed to ensure extinctions are avoided, the sustainability of more productive species is secured, and to avoid the continued thinning of the regional food security portfolio.

Blunted satellite cell response is associated with dysregulated IGF-1 expression after exercise with age - Daniel R. Moore; Bryon R. McKay; Mark A. Tarnopolsky; Gianni Parise (European Journal of Applied Physiology, 2018)

Climate research priorities for policy-makers, practitioners, and scientists in Georgia, USA - Murray A. Rudd; Althea F. P. Moore; Daniel Rochberg; Lisa Bianchi-Fossati; Marilyn A. Brown; David D’Onofrio; Carrie A. Furman; Jairo Garcia; Ben Jordan; Jennifer Kline; L. Mark Risse; Patricia L. Yager; et al. (Environmental Management, 2018)

Opportunities for an enhanced integration of neuroscience and genomics - Ashlee A. Moore; Chelsea Sawyers; Daniel E. Adkins; Anna R. Docherty (Brain Imaging and Behavior, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Survival rates indicate that correlations between community‐weighted mean traits and environments can be unreliable estimates of the adaptive value of traits - Daniel C. Laughlin; Robert T. Strahan; Peter B. Adler; Margaret M. Moore (Ecology Letters, 2018)
Correlations between community‐weighted mean ( CWM ) traits and environmental gradients are often assumed to quantify the adaptive value of traits. We tested this assumption by comparing these correlations with models of survival probability using 46 perennial species from long‐term permanent plots in pine forests of Arizona. Survival was modelled as a function of trait × environment interactions, plant size, climatic variation and neighbourhood competition. The effect of traits on survival depended on the environmental conditions, but the two statistical approaches were inconsistent. For example, CWM ‐specific leaf area ( SLA ) and soil fertility were uncorrelated. However, survival was highest for species with low SLA in infertile soil, a result which agreed with expectations derived from the physiological trade‐off underpinning leaf economic theory. CWM trait–environment relationships were unreliable estimates of how traits affected survival, and should only be used in predictive models when there is empirical support for an evolutionary trade‐off that affects vital rates.

Energy conserving thermoregulatory patterns and lower disease severity in a bat resistant to the impacts of white-nose syndrome - Marianne S. Moore; Kenneth A. Field; Melissa J. Behr; Gregory G. Turner; Morgan E. Furze; Daniel W. F. Stern; Paul R. Allegra; Sarah A. Bouboulis; Chelsey D. Musante; Megan E. Vodzak; Matthew E. Biron; Melissa B. Meierhofer; et al. (Journal of Comparative Physiology B, 2018)

A system to identify inhibitors of mTOR signaling using high-resolution growth analysis in Saccharomyces cerevisiae - Mitchell B. Lee; Daniel T. Carr; Michael G. Kiflezghi; Yan Ting Zhao; Deborah B. Kim; Socheata Thon; Margarete D. Moore; Mary Ann K. Li; Matt Kaeberlein (GeroScience, 2017)

Emergent climate and CO 2 sensitivities of net primary productivity in ecosystem models do not agree with empirical data in temperate forests of eastern North America - Christine R. Rollinson; Yao Liu; Ann Raiho; David J. P. Moore; Jason McLachlan; Daniel A. Bishop; Alex Dye; Jaclyn H. Matthes; Amy Hessl; Thomas Hickler; Neil Pederson; Benjamin Poulter; et al. (Global Change Biology, 2017)
Ecosystem models show divergent responses of the terrestrial carbon cycle to global change over the next century. Individual model evaluation and multimodel comparisons with data have largely focused on individual processes at subannual to decadal scales. Thus far, data‐based evaluations of emergent ecosystem responses to climate and CO 2 at multidecadal and centennial timescales have been rare. We compared the sensitivity of net primary productivity ( NPP ) to temperature, precipitation, and CO 2 in ten ecosystem models with the sensitivities found in tree‐ring reconstructions of NPP and raw ring‐width series at six temperate forest sites. These model‐data comparisons were evaluated at three temporal extents to determine whether the rapid, directional changes in temperature and CO 2 in the recent past skew our observed responses to multiple drivers of change. All models tested here were more sensitive to low growing season precipitation than tree‐ring NPP and ring widths in the past 30 years, although some model precipitation responses were more consistent with tree rings when evaluated over a full century. Similarly, all models had negative or no response to warm‐growing season temperatures, while tree‐ring data showed consistently positive effects of temperature. Although precipitation responses were least consistent among models, differences among models to CO 2 drive divergence and ensemble uncertainty in relative change in NPP over the past century. Changes in forest composition within models had no effect on climate or CO 2 sensitivity. Fire in model simulations reduced model sensitivity to climate and CO 2 , but only over the course of multiple centuries. Formal evaluation of emergent model behavior at multidecadal and multicentennial timescales is essential to reconciling model projections with observed ecosystem responses to past climate change. Future evaluation should focus on improved representation of disturbance and biomass change as well as the feedbacks with moisture balance and CO 2 in individual models.

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Smoking status, usual adult occupation, and risk of recurrent urothelial bladder carcinoma: data from The Cancer Genome Atlas (TCGA) Project - Amber N. Wilcox; Debra T. Silverman; Melissa C. Friesen; Sarah J. Locke; Daniel E. Russ; Noorie Hyun; Joanne S. Colt; Jonine D. Figueroa; Nathaniel Rothman; Lee E. Moore; Stella Koutros (Cancer Causes & Control, 2016)

Discovery and complete genome sequence of a novel circovirus-like virus in the endangered rowi kiwi, Apteryx rowi - Daniel J. White; Richard J. Hall; Jing Wang; Nicole E. Moore; Duckchul Park; Kate McInnes; Brett D. Gartrell; Daniel M. Tompkins (Virus Genes, 2016)

Controls over Ocean Mesopelagic Interior Carbon Storage (COMICS): Fieldwork, Synthesis, and Modeling Efforts - Richard J. Sanders; Stephanie A. Henson; Adrian P. Martin; Tom R. Anderson; Raffaele Bernardello; Peter Enderlein; Sophie Fielding; Sarah L. C. Giering; Manuela Hartmann; Morten Iversen; Samar Khatiwala; Phyllis Lam; et al. (Frontiers in Marine Science, 2016)

Highly heritable resistance to root-lesion nematode (Pratylenchus thornei) in Australian chickpea germplasm observed using an optimised glasshouse method and multi-environment trial analysis - M. S. Rodda; K. B. Hobson; C. R. Forknall; R. P. Daniel; J. P. Fanning; D. D. Pounsett; S. Simpfendorfer; K. J. Moore; K. J. Owen; J. G. Sheedy; J. P. Thompson; G. J. Hollaway; et al. (Australasian Plant Pathology, 2016)

Harnessing publicly available genetic data to prioritize lipid modifying therapeutic targets for prevention of coronary heart disease based on dysglycemic risk - Vinicius Tragante; Folkert W. Asselbergs; Daniel I. Swerdlow; Tom M. Palmer; Jason H. Moore; Paul I. W. de Bakker; Brendan J. Keating; Michael V. Holmes (Human Genetics, 2016)

Antibiotics as CECs: An Overview of the Hazards Posed by Antibiotics and Antibiotic Resistance - Geoffrey I. Scott; Dwayne E. Porter; R. Sean Norman; C. Hart Scott; Miguel I. Uyaguari-Diaz; Keith A. Maruya; Steve B. Weisberg; Michael H. Fulton; Ed F. Wirth; Janet Moore; Paul L. Pennington; Daniel Schlenk; et al. (Frontiers in Marine Science, 2016)

Prioritization of knowledge needs for sustainable aquaculture: a national and global perspective - Aisla C Jones; Angela Mead; Michel J Kaiser; Melanie C V Austen; Alex W Adrian; Neil A Auchterlonie; Kenneth D Black; Lucy R Blow; Charlotte Bury; Janet H Brown; Gavin M Burnell; Elaine Connolly; et al. (Fish and Fisheries, 2015)
Aquaculture is currently the fastest expanding global animal food production sector and is a key future contributor to food security. An increase in food security will be dependent upon the development and improvement of sustainable practices. A prioritization exercise was undertaken, focusing on the future knowledge needs to underpin UK sustainable aquaculture (both domestic and imported products) using a ‘task force’ group of 36 ‘practitioners’ and 12 ‘research scientists’ who have an active interest in sustainable aquaculture. A long list of 264 knowledge needs related to sustainable aquaculture was developed in conjunction with the task force. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge need. The top 25 knowledge needs are presented, as scored separately by ‘practitioners’ or ‘research scientists’. There was similar agreement in priorities identified by these two groups. The priority knowledge needs will provide guidance to structure ongoing work to make science accessible to practitioners and help to prioritize future science policy needs and funding. The process of knowledge exchange, and the mechanisms by which this can be achieved, effectively emerged as the top priority for sustainable aquaculture. Viable alternatives to wild fish‐based aquaculture feeds, resource constraints that will potentially limit expansion of aquaculture, sustainable offshore aquaculture and the treatment of sea lice also emerged as strong priorities. Although the exercise was focused on UK needs for sustainable aquaculture, many of the emergent issues are considered to have global application.

Comparison of low-carbon pathways for California - Geoffrey M. Morrison; Sonia Yeh; Anthony R. Eggert; Christopher Yang; James H. Nelson; Jeffery B. Greenblatt; Raphael Isaac; Mark Z. Jacobson; Josiah Johnston; Daniel M. Kammen; Ana Mileva; Jack Moore; et al. (Climatic Change, 2015)

Acute Methylenedioxypyrovalerone Toxicity - Blake A. Froberg; Michael Levine; Michael C. Beuhler; Bryan S. Judge; Philip W. Moore; Kristin M. Engebretsen; Nathanael J. Mckeown; Christopher D. Rosenbaum; Amy C. Young; Daniel E. Rusyniak (Journal of Medical Toxicology, 2015)

The value of plantation forests for plant, invertebrate and bird diversity and the potential for cross-taxon surrogacy - Sandra Irwin; Scott M. Pedley; Linda Coote; Anke C. Dietzsch; Mark W. Wilson; Anne Oxbrough; Oisín Sweeney; Karen M. Moore; Rebecca Martin; Daniel L. Kelly; Fraser J. G. Mitchell; Thomas C. Kelly; et al. (Biodiversity and Conservation, 2014)

Vestibular integrator neurons have quadratic functions due to voltage dependent conductances - Christophe Magnani; Daniel Eugène; Erwin Idoux; Lee E. Moore (Journal of Computational Neuroscience, 2013)

Predicting invasion in grassland ecosystems: is exotic dominance the real embarrassment of richness? - Eric W. Seabloom; Elizabeth T. Borer; Yvonne Buckley; Elsa E. Cleland; Kendi Davies; Jennifer Firn; W. Stanley Harpole; Yann Hautier; Eric Lind; Andrew MacDougall; John L. Orrock; Suzanne M. Prober; et al. (Global Change Biology, 2013)
Invasions have increased the size of regional species pools, but are typically assumed to reduce native diversity. However, global‐scale tests of this assumption have been elusive because of the focus on exotic species richness, rather than relative abundance. This is problematic because low invader richness can indicate invasion resistance by the native community or, alternatively, dominance by a single exotic species. Here, we used a globally replicated study to quantify relationships between exotic richness and abundance in grass‐dominated ecosystems in 13 countries on six continents, ranging from salt marshes to alpine tundra. We tested effects of human land use, native community diversity, herbivore pressure, and nutrient limitation on exotic plant dominance. Despite its widespread use, exotic richness was a poor proxy for exotic dominance at low exotic richness, because sites that contained few exotic species ranged from relatively pristine (low exotic richness and cover) to almost completely exotic‐dominated ones (low exotic richness but high exotic cover). Both exotic cover and richness were predicted by native plant diversity (native grass richness) and land use (distance to cultivation). Although climate was important for predicting both exotic cover and richness, climatic factors predicting cover (precipitation variability) differed from those predicting richness (maximum temperature and mean temperature in the wettest quarter). Herbivory and nutrient limitation did not predict exotic richness or cover. Exotic dominance was greatest in areas with low native grass richness at the site‐ or regional‐scale. Although this could reflect native grass displacement, a lack of biotic resistance is a more likely explanation, given that grasses comprise the most aggressive invaders. These findings underscore the need to move beyond richness as a surrogate for the extent of invasion, because this metric confounds monodominance with invasion resistance. Monitoring species' relative abundance will more rapidly advance our understanding of invasions.

Big claims for big weights but with little evidence - Nicholas A. Burd; Daniel R. Moore; Cameron J. Mitchell; Stuart M. Phillips (European Journal of Applied Physiology, 2013)

Similar increases in muscle size and strength in young men after training with maximal shortening or lengthening contractions when matched for total work - Daniel R. Moore; Mark Young; Stuart M. Phillips (European Journal of Applied Physiology, 2012)

Effects of biotic disturbances on forest carbon cycling in the U nited S tates and C anada - Jeffrey A. Hicke; Craig D. Allen; Ankur R. Desai; Michael C. Dietze; Ronald J. Hall; Edward H. (Ted) Hogg; Daniel M. Kashian; David Moore; Kenneth F. Raffa; Rona N. Sturrock; James Vogelmann (Global Change Biology, 2012)
Forest insects and pathogens are major disturbance agents that have affected millions of hectares in N orth A merica in recent decades, implying significant impacts to the carbon ( C ) cycle. Here, we review and synthesize published studies of the effects of biotic disturbances on forest C cycling in the U nited S tates and C anada. Primary productivity in stands was reduced, sometimes considerably, immediately following insect or pathogen attack. After repeated growth reductions caused by some insects or pathogens or a single infestation by some bark beetle species, tree mortality occurred, altering productivity and decomposition. In the years following disturbance, primary productivity in some cases increased rapidly as a result of enhanced growth by surviving vegetation, and in other cases increased slowly because of lower forest regrowth. In the decades following tree mortality, decomposition increased as a result of the large amount of dead organic matter. Net ecosystem productivity decreased immediately following attack, with some studies reporting a switch to a C source to the atmosphere, and increased afterward as the forest regrew and dead organic matter decomposed. Large variability in C cycle responses arose from several factors, including type of insect or pathogen, time since disturbance, number of trees affected, and capacity of remaining vegetation to increase growth rates following outbreak. We identified significant knowledge gaps, including limited understanding of carbon cycle impacts among different biotic disturbance types (particularly pathogens), their impacts at landscape and regional scales, and limited capacity to predict disturbance events and their consequences for carbon cycling. We conclude that biotic disturbances can have major impacts on forest C stocks and fluxes and can be large enough to affect regional C cycling. However, additional research is needed to reduce the uncertainties associated with quantifying biotic disturbance effects on the N orth A merican C budget.

The Business of Forest Enterprise / Urban Ecosystems - Steve Narolski; Richard Bin Mei; Rafael De La Torre; Mike Clutter; John Pait; Maggi Kelly; Frederick Cubbage; Patricio MacDonagh; Gustavo Balmelli; Virginia Morales Olmos; Adriana Bussoni; Rafael Rubilar; et al. (Journal of Forestry, 2011)
22In 2009, five unique methods were used to inspect vegetation-related conditions along Bonneville Power Administration (BPA) rights-of-way (ROW). Some methods were trials that BPA committed to execute as part of a settlement with its regional regulatory organization, the Western Electric Coordination Council (WECC), for violations of reliability standards from vegetation grow-in related outages. A combination of simple, stratified, and 100% sampling were used to compare and contrast each inspection technique. A cost-replacement comparison between all inspection techniques was performed, weighting efficacy of one technique to another in the form of replacement value. Cost-benefit and return-on-investment analyses were also computed. From these analyses, LiDAR proved most effective in identifying vegetation related clearance issues but proved most costly, at least for initial establishment. The average cost of LiDAR trended downward with subsequent flights. The most cost effective method was using helicopters with either Natural Resource Specialists (NRS) or Transmission Line Maintenance (TLM) personnel serving as aerial observers, but this methodology proved the most inaccurate. Furthermore, the ancillary utility of LiDAR for related asset assessments more than justify the initial expense, includes power line sag ratings, asset (structures, insulators, roads, etc.) health, and encroachment identification. It is hypothesized that incorporating LiDAR sampling from 20% of the whole system per year to 40+ % may actually represent a cost-savings when allocating available resources system-wide. This data can also be used for documenting compliance with all federal regulations and requirements, as well as substitute for manual on-the-ground inspections, whether by BPA staff or third-party contractors.

Paternal occupational exposure to pesticides and risk of neuroblastoma among children: a meta-analysis - Amy Moore; Daniel A. Enquobahrie (Cancer Causes & Control, 2011)

Nutrient provision increases signalling and protein synthesis in human skeletal muscle after repeated sprints - Vernon G. Coffey; Daniel R. Moore; Nicholas A. Burd; Tracy Rerecich; Trent Stellingwerff; Andrew P. Garnham; Stuart M. Phillips; John A. Hawley (European Journal of Applied Physiology, 2011)

Stability and Broad-sense Heritability of Mineral Content in Potato: Zinc - Charles Raymond Brown; Kathleen G. Haynes; Martin Moore; Mark J. Pavek; Daniel C. Hane; Steven L. Love; Richard G. Novy; J. Creighton Miller (American Journal of Potato Research, 2011)

Intrinsic membrane properties of central vestibular neurons in rodents - Daniel Eugène; Erwin Idoux; Mathieu Beraneck; L. E. Moore; Pierre-Paul Vidal (Experimental Brain Research, 2011)

Preferences for Timing of Wetland Loss Prevention in Louisiana - Daniel R. Petrolia; Ross G. Moore; Tae-goun Kim (Wetlands, 2011)

Evidence for indirect effects of plant diversity and composition on net nitrification - Daniel C. Laughlin; Stephen C. Hart; Jason P. Kaye; Margaret M. Moore (Plant and Soil, 2010)

Powering an Implantable Minipump with a Multi-layered Printed Circuit Coil for Drug Infusion Applications in Rodents - Tina K. Givrad; Jean-Michel I. Maarek; William H. Moore; Daniel P. Holschneider (Annals of Biomedical Engineering, 2010)

Quantifying structural physical habitat attributes using LIDAR and hyperspectral imagery - Robert K. Hall; Russell L. Watkins; Daniel T. Heggem; K. Bruce Jones; Philip R. Kaufmann; Steven B. Moore; Sandra J. Gregory (Environmental Monitoring and Assessment, 2009)

Prevalence and type distribution of human papillomavirus in 5,000 British Columbia women—implications for vaccination - Richard A. Moore; Gina Ogilvie; Daniel Fornika; Veronika Moravan; Marc Brisson; Mahsa Amirabbasi-Beik; Anita Kollar; Thomas Burgess; Ray Hsu; Laura Towers; Jane Lo; Jasenka Matisic; et al. (Cancer Causes & Control, 2009)

Soil solution and sugar maple response to NH4NO3 additions in a base-poor northern hardwood forest of Québec, Canada - Jean-David Moore; Daniel Houle (Environmental Monitoring and Assessment, 2009)

Reduced folate carrier 80A→G polymorphism, plasma folate, and risk of placental abruption - Cande V. Ananth; Morgan R. Peltier; Dirk F. Moore; Wendy L. Kinzler; Daniel Leclerc; Rima R. Rozen (Human Genetics, 2008)

Restoring plant species diversity and community composition in a ponderosa pine-bunchgrass ecosystem - Daniel C. Laughlin; Jonathan D. Bakker; Mark L. Daniels; Margaret M. Moore; Cheryl A. Casey; Judith D. Springer (Plant Ecology, 2008)

Spatial variability of stable isotopes and fossil pigments in surface sediments of Alaskan coastal lakes: Constraints on quantitative estimates of past salmon abundance - Curtis S. Brock; Peter R. Leavitt; Daniel E. Schindler; Susan P. Johnson; Jonathan W. Moore (Limnology and Oceanography, 2006)
We quantified spatial patterns of stable isotopes of N and C (δ 15 N, δ 13 C) and fossil pigment concentrations in the uppermost 10 mm of sediment (,10 yr) from 74 profundal locations and three spawning‐stream discharge areas in Lake Nerka, southwest Alaska. Sediment δ 15 N (4.3% ± 0.7%) and δ 13 C (−26.3% ± 1.2%) varied directly (δ 15 N) or inversely (δ 13 C) with water column depth, whereas concentrations of most fossil pigments from algae were negatively correlated with depth. Sediment δ 15 N and δ 13 C were poorly correlated with either fossil pigment abundance or the local densities of spawning salmon. Instead, coastal nursery lakes appeared to integrate marine‐derived nutrients rapidly into lakewide nutrient pools, suggesting that while individual cores may be used to reconstruct whole‐lake salmon densities, habitat‐specific variations of past fish populations cannot be quantified reliably from sedimentary analyses.

HLA-E, HLA-F, and HLA-G polymorphism: genomic sequence defines haplotype structure and variation spanning the nonclassical class I genes - Chul-Woo Pyo; Luke M. Williams; Yuki Moore; Hironobu Hyodo; Shuying Sue Li; Lue Ping Zhao; Noriko Sageshima; Akiko Ishitani; Daniel E. Geraghty (Immunogenetics, 2006)

Sterol carrier protein-2 expression alters sphingolipid metabolism in transfected mouse L-cell fibroblasts - Daniel G. Milis; Messiah K. Moore; Barbara P. Atshaves; Friedhelm Schroeder; John R. Jefferson (Molecular and Cellular Biochemistry, 2006)

Disturbance of freshwater habitats by anadromous salmon in Alaska - Jonathan W. Moore; Daniel E. Schindler; Mark D. Scheuerell (Oecologia, 2004)

An ancient linked fluid migration system: cold-seep deposits and sandstone intrusions in the Panoche Hills, California, USA - Hilde Schwartz; James Sample; Kevin D. Weberling; Daniel Minisini; J. Casey Moore (Geo-Marine Letters, 2003)

Approaches for Quantifying the Metabolism of Physical Economies: Part I: Methodological Overview - Peter L. Daniels; Stephen Moore (Journal of Industrial Ecology, 2001)
Summary This article is the first of a two‐part series that describes and compares the essential features of nine existing “physical economy” approaches for quantifying the material demands of the human economy upon the natural environment. A range of material flow analysis (MFA) and related techniques is assessed and compared in terms of several major dimensions. These include the system boundary identification for material flow sources, extents, and the key socioinstitutional entities containing relevant driving forces, as well as the nature and detailing of system components and flow interconnections, and the comprehensiveness and types of flows and materials covered. Shared conceptual themes of a new wave of physical economy approaches are described with a brief overview of the potential applications of this broad family of methodologies. The evolving and somewhat controversial nature of the characteristics and role that define MFA is examined. This review suggests the need to specify whether MFA is a general metabolic flow measurement procedure that can be applied from micro to macrolevels of economic activity, or a more specific methodology aimed primarily at economy‐wide analyses that “map” the material relations between society and nature. Some alternative options for classifying MFA are introduced for discussion before a more detailed comparative summary of the key methodological features of each approach in the second part of this two‐part article. The review is presented (1) as a reference and resource for the increasing number of policy makers and practitioners involved in industrial ecology and the evaluation of the material basis of economies and the formulation of eco‐efficiency strategies, and (2) to provoke discussion and ongoing dialogue to clarify the many existing areas of discordance in environmental accounting related to material flows, and help consolidate the methodological basis and application of MFA.

Evolutionary conservation, developmental expression, and genomic mapping of mammalian Twisted gastrulation - Daniel Graf; Paula M. Timmons; Megan Hitchins; Vasso Episkopou; Gudrun Moore; Takekito Ito; Asao Fujiyama; Amanda G. Fisher; Matthias Merkenschlager (Mammalian Genome, 2001)

Notes - E. A. Stokdyk; W. H. Olin; G. S. Kelch; J. T. Quinn; B. A. Brown; Lou D. Sweet; H. C. Moore; Daniel Dean; J. G. Milward (American Journal of Potato Research, 1928)

Disease control and seed improvement number - F. A. Krantz; Donald Folsom; Daniel Dean; H. C. Moore; J. Tucker; J. W. Weston; H. R. Talmage; George L. Zundel; M. F. Barrus; G. L. Tiebout; Walter M. Peacock; C. L. Fitch; et al. (American Journal of Potato Research, 1925)

Kiwanians sponsor potato club work - P. R. Young; E. V. Hardenburg; B. E. Brown; Paul M. Williams; Daniel Dean; A. G. Waller; H. R. Talmage; H. C. Moore; J. G. Milward; W. Stuart; H. B. Stevens; R. W. Goss; et al. (American Journal of Potato Research, 1925)

Potato notes - C. Tice; W. C. Edmundson; Ray D. Hews; H. C. Moore; H. O. Werner; W. H. Martin; Daniel Dean; W. A. McCubbin; W. H. Zimmerly (American Journal of Potato Research, 1924)

Potato notes - Lou D. Sweet; J. H. Woolf; A. E. Wilkinson; F. C. Gaylord; E. A. Stodyke; R. D. Hews; H. C. Moore; J. W. Weston; W. V. Longley; J. Norton Woodruff; W. H. Martin; J. C. Crissey; et al. (American Journal of Potato Research, 1924)